Sustainable Business Models and IT Innovation: The Case of the REMIT - Svitlana Kolosok; Serhiy Lyeonov; Iryna Voronenko; Olena Goncharenko; Julia Maksymova; Oksana Chumak (Journal of Information Technology Management)
This paper aimed to explore IT innovations used in sustainable business models in the European single energy market. For this purpose, the academic literature and content analyses of organized marketplaces were performed. The results showed that end users are not always interested in changing the service and try to choose services/resources well known to them. At the same time, market operators see the need for radical change by introducing strategic innovations and digitizing energy markets. Sustainable e-government management models are typically sustained by IoT, blockchain, and smart grid management technologies.